Hip Arthroscopy for Labral Tears in Workers' Compensation: A Matched-Pair Controlled Study. (October 2013) - Stake, Christine E.; Jackson, Timothy J.; Stone, Jennifer C.; Domb, Benjamin G.
Background: Workers' compensation (WC) status has been related to clinical outcomes; however, no comparative studies have been performed to assess 2-year outcomes between hip arthroscopy patients based on WC status. Purpose: To evaluate 2-year outcomes of patients receiving WC who underwent hip arthroscopy for labral tears and to compare outcomes with those of a matched control group not receiving WC. Study Design: Cohort study; Level of evidence, 3. Methods: During the study period between June 2008 and August 2010, data were collected on all patients treated with hip arthroscopy. Inclusion criteria for the study group were diagnosis of labral tear and WC status. All patients were assessed pre- and postoperatively with 4 patient-reported outcome (PRO) measures: the modified Harris Hip Score (mHHS), Non-Arthritic Hip Score (NAHS), Hip Outcome Score–Activities of Daily Living (HOS-ADL), and Hip Outcome Score–Sport-Specific Subscales (HOS-SSS). Pain was estimated on the visual analog scale (VAS), and satisfaction was measured on a scale from 0 to 10. A matched-pair group of patients not associated with WC was selected in a 1:1 ratio according to age within 3 years, sex, surgical procedures, and radiographic findings. Results: Twenty-one hips were included in each group. Patients with WC status had significantly lower preoperative PRO scores for all measures ( P < .001). However, there was no significant difference between VAS pain scores between the groups. Of the WC patients, 86% returned to work at a median 82 days postoperatively. For the WC group, the score improvement from preoperative to 2-year follow-up was 46 to 67.7 for mHHS, 39.3 to 66 for NAHS, 39.7 to 69.5 for HOS-ADL, and 15.3 to 49.8 for HOS-SSS. For the control group, the score improvement from preoperative to 2-year follow-up was 67.9 to 85.8 for mHHS, 62.6 to 84.4 for NAHS, 69.8 to 86.9 for HOS-ADL, and 41.9 to 73.8 for HOS-SSS. Both groups demonstrated statistically significant postoperative improvement in all scores, and the average amount of change of preoperative to postoperative scores between the 2 groups was only significantly different for the HOS-ADL in the control group ( P = .043). However, the WC group demonstrated greater improvement in aggregate scores in the HOS-ADL. Pain scores decreased from 7 to 3.9 in the WC group and 5.8 to 3.2 in the control group and were not significantly different between the groups. Patient satisfaction was 6.8 for the WC group and 7.7 for the control group, with no significant difference between groups. Conclusion: Our study demonstrated that WC patients had significantly lower baseline PRO scores when compared with a matched-pair control group. However, both groups demonstrated statistically significant postoperative improvement in all scores. Patients with WC status started and ended with lower absolute scores but benefited from arthroscopic intervention for hip injuries. While patient and physician expectations may be adjusted accordingly, these results may reflect favorably on the use of hip arthroscopy for labral tears in the WC population.